Non-invasive Diagnosis of Antinephrin–Associated Podocytopathy - Felicitas E. Hengel; Michelle C.Z. Chong; Wing Yin Leung; Silke Dehde; Anne Mühlig; Matthias Janneck; Henry H.L. Wu; Tobias B. Huber; Arvind Ponnusamy; Nicola M. Tomas (Kidney International Reports)
Introduction: Circulating autoantibodies against the podocyte surface protein nephrin have recently been described in patients with podocytopathies, that is, minimal change disease, primary focal segmental glomerulosclerosis, and childhood idiopathic nephrotic syndrome. Their high specificity for podocytopathies in combination with a strong correlation with disease activity hold the potential for a non-invasive diagnosis, but prospective data are lacking. Methods: Here, we describe 3 patients with contraindications or unwillingness for a kidney biopsy, hampering a timely histological diagnosis and choice of appropriate therapy. Results: In all patients, antinephrin autoantibodies were detected by quantitative immunoprecipitation, prompting the initiation of adequate treatment. These interventions induced a decrease in antinephrin autoantibody levels and clinical remission. Conclusion: Our study highlights the potential of antinephrin autoantibody measurement for a noninvasive diagnosis of antinephrin-associated podocytopathy.